2022
DOI: 10.1002/ajh.26768
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in reduced‐intensity hematopoietic cell transplantation based on donor availability in patients aged 50–75 with advanced myelodysplastic syndrome: BMT CTN 1102

Abstract: For myelodysplastic syndrome (MDS), allogeneic hematopoietic cell transplantation (alloHCT) is the only available curative therapy. The Blood and Marrow Transplant Clinical Trials Network study 1102 (BMT CTN 1102, NCT02016781) was a multicenter, biologic assignment trial based on matched donor availability in adults aged 50-75 with higher risk de novo MDS who were candidates for reduced-intensity conditioning (RIC) alloHCT. The primary analysis showed that those who received alloHCT had a survival benefit, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(32 reference statements)
2
7
0
Order By: Relevance
“…The researchers concluded that the survival advantage for patients who underwent alloHCT did not come at the cost of worse quality of life. 12 The results also showed baseline QOL was a consistent predictor of survival outcomes and subsequent QOL outcomes. Two studies from the Center for International Blood and Marrow Transplant Research (CIBMTR) also showed PROs can be an indicator of post-HCT outcomes and QOL.…”
Section: Hemonc Timesmentioning
confidence: 81%
See 1 more Smart Citation
“…The researchers concluded that the survival advantage for patients who underwent alloHCT did not come at the cost of worse quality of life. 12 The results also showed baseline QOL was a consistent predictor of survival outcomes and subsequent QOL outcomes. Two studies from the Center for International Blood and Marrow Transplant Research (CIBMTR) also showed PROs can be an indicator of post-HCT outcomes and QOL.…”
Section: Hemonc Timesmentioning
confidence: 81%
“…Patients who underwent HCT, as well as those who did not, had similar PRO trajectories. The researchers concluded that the survival advantage for patients who underwent alloHCT did not come at the cost of worse quality of life 12…”
mentioning
confidence: 99%
“…To account for missing surveys and to develop an approach to extrapolate results across the time period of interest, we generated an inverse probability weighted independent estimating equations (IPW-IEE) model. Using the IPW-IEE model similar to a recent analysis of health-related QOL for BMT 1102 participants, 3 we generated monthly utility values for individuals from survey results.…”
Section: Methodsmentioning
confidence: 99%
“…16 Of note, an evaluation of trial participants completing several different PRO measures found no significant differences in QOL between patients in the donor and no-donor arms across several physical, social, and emotional well-being domains, and an overall trend of improvement in QOL among transplant patients after 6 months. 3 Although the clinical results of BMT 1102 were similar for older persons who are typically covered by commercial insurance (those age 50-64 years), the economic evidence is less compelling. The projected survival benefit in this population (3.4 life-years) is high compared with other common treatments for advanced cancer, including hematologic malignancies, in this age group.…”
Section: Secondary Analysis (By Treatment Received)mentioning
confidence: 99%
See 1 more Smart Citation